Penerapan Model Pembelajaran Saintifik Dalam Meningkatkan Pemahaman Siswa Sekolah Dasar - Nurul Faizah Romli (Impressive: Journal of Education, 2024)
This study aims to enhance the understanding of fourth-grade students in the theme "Indahnya Negeriku" through the implementation of the scientific learning model. Based on pre-cycle conditions showing difficulties in understanding the concepts of environmental conservation, map-making, and cardinal directions, this research was conducted in three cycles to address these issues. The method used is a quasi-experimental approach with the application of video-based learning, discussions, and practical activities. The results of the study show significant improvements in each cycle. In the first cycle, students’ understanding of environmental conservation reached 70%, map-making skills were 65%, and participation in discussions was 60%. The second cycle showed 80% understanding of cardinal directions, 70% ability to draw classroom maps, and 75% participation in discussions. In the third cycle, students' understanding of historical tourist sites reached 85%, presentation skills were 75%, and participation in discussions was 80%. Although some challenges, such as difficulties in accurate drawing, were encountered, this research indicates that the scientific learning model significantly improves student involvement and understanding.